Perancangan Meja Pencekam dan Kursi Guna Memperbaiki Postur Kerja berdasarkan Pendekatan Anthropometri di Lathan Furniture - Prasetyaningrum, Fitri; Rochman, Taufiq; Iftadi, Irwan (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2010)
Work activities at the dining chair assembly station in Lathan Furniture are still simple. Based on the results of the Nordic Body Map questionnaires which are distributed to the five workers, worker injured muscles in the lower neck (80%), shoulder (20%), back (40%), waist (40%), hips (20%), buttocks (20%), thigh (40%), knee (60%), and calf (80%). And based on the Rapid Entire Body Assessment in the activity of weaving the back seat, turning the chair and putting a chair after being reversed, all of this activities are in a higher level with the REBA score of 11, 9, and 8. While the movement of the front seat weaving, weaving the sides of the legs of the chair, and wicker chair leg, all of this activities have REBA score 4, 5, and 4. To improve working posture at this time, it is necessary to design clamp table and chairs based on anthropometric approach. From the assessment results of working posture with the REBA method, workers’ working posture has improved after using the work facility design result. On the front chair weaving movement decreased level, from level 2 to level 1, the rear backrest weaving movements decreased level from level 3 to level 2, braided chair leg movements also decreased level, from level 2 to level 1. That can be concluded that the result design of chuck table and chair can improve working posture of the workers.